The Freezing Process of Red Snapper (Lutjanus malabaricus) with the Air Blast Freezing (ABF) Method at PT. Inti Luhur Fuja Abadi, Pasuruan, East Java - Gabriel Zola Scriptura; endang dewi masithah (Journal of Marine and Coastal Science, 2021)
Fish is a protein source that is very potential and needed by humans. One of the fish that has a high enough nutrient content is Red Snapper (Lutjanus malabaricus). Snapper fish contains 92 kilocalories of energy, 20 grams of protein, 0 grams of carbohydrates, 0.7 grams of fat, 20 milligrams of calcium, 200 milligrams of phosphorus, and 1 milligram of iron. The high water content is one potential that must be considered because it is a good medium for microbial growth. Therefore efforts are needed to maintain the nutritional content, freshness, taste, and extend the shelf life through preservation, one of which is by freezing. The Air Blast Freezing method is one of the freezing methods that uses a combination of low temperatures which are temperatures of -35℃ to -40℃ by blowing cold air  quickly towards the product. This method has the advantage of one of which is relatively easy operation. The purpose of this field work practice is to know the process of freezing Red Snapper (Lutjanus malabaricus) with the Air Blast Freezing (ABF) method and the obstacles in the production of Red Snapper (Lutjanus malabaricus) using the Air Blast Freezing (ABF) method. The stages of the production process of Red Snapper (Lutjanus malabaricus) are the reception of raw materials, washing I, sorting, washing II, weighing, washing III, preparation, freezing with the Air Blast Freezing (ABF) method, glazing, packaging, storaging, stuffing. The freezing process with the Air Blast Freezing (ABF) method uses a temperature of -35℃ to -40℃ for 6-8 hours so that the plant can produce as much as 3 tons in one day. Obstacles to the freezing process at PT ILUFA are raw materials that contain parasites. Factors that influence the freezing process include raw materials during the reception and monitoring process during the freezing process in the ABF engine.